Perencanaan Partisipatif Jalur Evakuasi dan Titik Kumpul Desa Ngargomulyo dalam Upaya Pengurangan Resiko Bencana Gunungapi Merapi - Wulan Mei, Estuning Tyas; Rachmawati, Rini (The ITB Journal Publisher, 2016)
Abstract. Community involvement in the planning of evacuation routes and meeting points is necessary to make the result suitable for the communityâs needs and the conditions in their environment. Ngargomulyo Village, located 6.5 km from the peak of Merapi Volcano, needs evacuation planning as an effort in disaster risk reduction. Against the background of the urgency of establishing emergency evacuation routes for Ngargomulyo Village and the need for community involvement in the planning process, this paper presents a participatory planning of evacuation routes and meeting points for this village. The method used involved focus group discussion in view of producing an adequate evacuation map. All possible evacuation routes were evaluated by the community. According to the evacuation scheme, the inhabitants of the local settlements first have to go to the meeting point of their own settlement (titik kumpul dusun) and then move on to the village meeting point (titik kumpul desa) and next to the refugee camp in Tamanagung Village. An alternative scheme involves direct evacuation to Desa Tamangung without going through the village meeting point. Limited number of alternative evacuation routes creates the needs of structural and non structural developments to enable a smooth evacuation of the village community.Â Keywords. Merapi, Participatory Planning, Evacuation.